Use of the frame structures in the systems of coordination and control of complex of batch vacuum pans - Прокопенко, Юрий Владимирович; Ладанюк, Анатолий Петрович; Сокол, Ростислав Михайлович (Technology audit and production reserves, 2015)
The definition of new requirements for the control of technological complexes of sugar raises the problem of development and implementation of innovative control systems. Solving these problems is fully possible only when using intelligent control systems. A promising direction is the development and implementation of case control systems. The work was developed a two-level frame structure for coordination and control of the technological complex of batch vacuum pans. The resulting two-level frame structure is defined in the format of categories: Action – A, situations – S, parameters – D. This structure allows constructing multi-level hierarchical control systems, and allows to quickly changing the control system with the help of script tools. Application of the proposed structure of frame type of case control systems (agent-based systems) allow more efficient, on a qualitative level, to lead the process of mass crystallization of sugar, integrated technological systems in multilevel hierarchical control systems. A promising area of application of multi-level frame systems is the use of their knowledge bases and decision-making systems of administrative and technical control systems.